Evaluating the Level of Cognitive domain for Postgraduate Summative Assessment in Forensic Medicine - Datta , A; Tiwari, P; Galoria, D; Rana , P; Shukla, S; Aggarwal S; Goswami , D (Journal of Indian Academy of Forensic Medicine, 2024)
Summative assessments hold significant sway over a student’s learning journey. However, there is a noticeable scarcity of literature addressing the validity of postgraduate summative assessment question papers within the domain of Forensic Medicine & Toxicology. This study endeavours to fill this gap by scrutinizing 48 question papers sourced from 12 healthcare universities spanning India for the year 2023. The question paper was evaluated based on several criteria, which included employment of structured & unstructured questions, presence or absence of action verb, distribution of marks based on competencies & level of cognitive domain assessed. From the results of the study, the content validity of the postgraduate summative question papers in Forensic Medicine and Toxicology fell short of expectations. This underscores the imperative for a comprehensive evaluation of the clarity and effectiveness of the blueprints employed by universities. It is evident that faculty training is indispensable to inspire and catalyse a shift in mindset, ultimately leading to a course correction.